Windows of opportunity and seasoned equity offerings: An empirical study - K. R. Naveen Kumar; Iqbal Thonse Hawaldar; T. Mallikarjunappa (Cogent Economics & Finance, 2018)
Taking a sample of seasoned equity offerings (SEOs) by firms listed on Bombay Stock Exchange (BSE) from the year 1992 to 2012, we examine two of the key issues concerning SEOs. First, whether SEOs are underpriced, issued at a price lower than the prevailing market price; and second, whether companies time their issues. Study of 162 SEOs exhibits significant underpricing at 1% significance level leading us to conclude that SEOs in India are significantly underpriced. Analysis of abnormal returns for 114 SEOs taking different event windows surrounding issue opening dates reveals that, except for the −1 to + 1 event window, CAAR for all other event windows are significantly negative. This leads us to conclude that investors in India experience significantly negative abnormal returns surrounding SEO issue opening. Overall, findings of the study reveal that SEOs in India are underpriced and that there exist windows of opportunity for SEOs in India.
Keywords: G12; 330; seasoned equity offerings; underpricing; windows of opportunity; abnormal returns